Gaiacells: A Housing Solution Proposal to Shantytowns from the Agricultural Cooperative Sphere. Socioeconomic, Tax, and Architectural Aspects - Luque Mateo, Miguel Ángel; Rueda Guerrero, Lourdes; Luque de Haro, Víctor Antonio (REVESCO. Revista de Estudios Cooperativos, 2024)
This paper aims to provide an innovative and original solution to the need for decent accommodation for agricultural workers living in shacks and substandard housing from a multidisciplinary perspective (socio-economic, legal-tax and architectural) on the basis of the so-called Nuclei of Transitional Accommodation for Integration, making it possible to finance their implementation from the agricultural cooperative sector, through the education and promotion fund, in compliance with the cooperative principle of community interest and the requirements of corporate social responsibility. The materialization of this objective in collaboration with institutions and entities of the Third Sector would allow the cooperatives to take advantage of the extensive tax benefits contained in the Ley de Régimen Fiscal de Entidades Sin Ánimo de Lucro, in addition to reinforcing productivity, social integration and the image of the Spanish agricultural industry. The proposal includes an architectural design based on the construction technique applied in the superadobe domes, intended to provide accommodation and services for 500 people in a parcel formed by different groups of quality bioclimatic buildings, simple, low cost and quick construction, covering all the necessary parameters in terms of health, safety, energy and thermal efficiency, anti-fire measures and high seismic resistance, adaptable to various needs, which makes this model a solution to the housing problem in general. Precisely, the sustainability, aesthetics and inclusiveness of the proposal have made it worthy of the support of the European Commission, through the local initiatives of the New European Bauhaus.
Keywords: Slums; cooperative principle of community interest; cooperative education and promotion fund; tax incentives; superadobe